Overall acceptability of the MNH-EPI-COS. - Karen Klein (6650600) (2025)
The Maternal and Newborn Health Core Outcome Set during Epidemics (MNH-EPI-COS) is a standardized set of outcomes developed to harmonize outcome selection in maternal and neonatal health research conducted during outbreaks and epidemics. It was developed through a four-stage modified Delphi process involving a large group of international stakeholders who assessed outcomes relevance through online surveys, followed by consensus meetings with a subgroup of stakeholders to finalize the COS. The objective of this study is to evaluate the acceptability of the full MNH-EPI-COS among key stakeholders who participated in the first two round of the Delphi process, to identify anticipated barriers to its adoption, and to assess agreement on the inclusion of individual outcomes, their definitions, and the perceived feasibility of data collection. An online consultation was conducted using an electronic semi-structured survey targeting senior clinical and public health experts and civil society representatives who had contributed to earlier phases of MNH-EPI-COS development but did not participate in the final consensus meetings. Of the 118 invited stakeholders, 100 completed the survey. The majority (95%) agreed that the MNH-EPI-COS captures the most important outcomes, is likely acceptable to key stakeholders (94%), and facilitates timely evidence generation (92%). Additionally, 75% expressed intent to use it. Over 80% of participants agreed with the individual outcomes and their definitions, except for “skin-to-skin contact” and “breastfeeding,” which were acceptable to 67% and 74%, respectively. Concerns were raised about the feasibility of measuring specific outcomes across diverse settings due to the substantial effort and resources required. Key barriers to adoption include knowledge, skills, and understanding gaps and the lack of practical resources. The MNH-EPI-COS, including its outcomes and definitions, was highly acceptable to the larger group of stakeholders involved in the early stages of its development. However, feasibility concerns remain. Successful implementation will require effective dissemination, targeted training, data collection resources, and real-world evaluation.